Characterisation of volatile profile and sensory analysis of fresh-cut "Radicchio di Chioggia" stored in air or modified atmosphere. (1st February 2016) - Cozzolino, Rosaria; Martignetti, Antonella; Pellicano, Mario Paolo; Stocchero, Matteo; Cefola, Maria; Pace, Bernardo; De Giulio, Beatrice
Highlights: VOCs profiles of fresh-cut "Radicchio di Chioggia" samples were compared by SPME. VOCs could be potential biomarkers under different packaging conditions. Comprehensive data analysis based on PLS regression models. Correlation between VOCs profile and sensory attributes was achieved. Abstract: The volatile profile of two hybrids of "Radicchio di Chioggia", Corelli and Botticelli, stored in air or passive modified atmosphere (MAP) during 12 days of cold storage, was monitored by solid phase micro-extraction (SPME) GC–MS. Botticelli samples were also subjected to sensory analysis. Totally, 61 volatile organic compounds (VOCs) were identified in the headspace of radicchio samples. Principal component analysis (PCA) showed that fresh product possessed a metabolic content similar to that of the MAP samples after 5 and 8 days of storage. Projection to latent structures by partial least squares (PLS) regression analysis showed the volatiles content of the samples varied depending only on the packaging conditions. Specifically, 12 metabolites describing the time evolution and explaining the effects of the different storage conditions were highlighted. Finally, a PCA analysis revealed that VOCs profile significantly correlated with sensory attributes.